آراء البصريين والكوفيين عن الإضافة في شرح ابن عقيل لألفية ابن مالك - Hafisuddin, Hafisuddin (Jurnal Al-Hibru, 2024)
One of the characteristics of language is system. The Bashrah scholars and the Kufa scholars are the two most famous madhhabs of nahwu scholars until now. In this study, researchers analyzed the opinions of Bashrah scholars and Kufa scholars by conducting: 1) What is the opinion of the scholars of Bashrah about idhafah in the book of syarah Ibn Aqil? 2) What is the opinion of the Kufa scholars about idhafah in the book of Sharh Ibn Aqil? 3) Explaining how the opinions of the scholars of Bashrah and the scholars of Kufa in the book of syarah Ibn Aqil. The purpose of this study is to find out the opinions of Bashrah scholars and Kufa scholars about idhafah in the book of syarah Ibn Aqil and to find out how the opinions of the two scholars. This research is using a qualitative approach with descriptive methods, from the object of this type of research is library research and content analysis. The opinions of the Bashrah scholars in the book of Ibn Aqil are 8 opinions while the opinions of the Kufa scholars are 4 opinions regarding the legal issues of idhafah. The results of this study are: The opinions of Bashrah scholars and Kufa scholars obtained in the book of sarah ibn aqil include. The understanding of lafaz لبيك, the law of mudhaf, the use of the sentence أذا, the use of the sentence لدن, the use of the sentence مع, throwing mudhaf, mudhaf to the number.